Forcible protection of civilians : the international legal framework for peace operations / Hanna Bourgeois. - Bourgeois, Hanna (Intersentia, 2024)
Discover essential insights into the international legal framework for protecting civilians in peace operations with Forcible Protection of Civilians. This analysis explores legal bases, UN mandates, and the interplay between mandates and human rights/international humanitarian law. Ideal for scholars and practitioners, this resource tackles complex legal nuances surrounding the use of force to ensure civilian safety in peace operations.